Investigation of fluid flow pattern in a 3D meandering tube - Ibrahim, Syed; Khan Marwat, Dil Nawaz; Ullah, Naeem; Nisar, Kottakkaran Sooppy (Frontiers in Materials, 2023)
Several types of meandering channels and their mathematical simulation have been proposed and discussed widely in the open literature. However, Poiseuille flow with streamwise vortices has been discussed inside a sinusoidal wavy meandering tube of nonuniform radius. In the present study, a novel geometry of the meandering tube has been taken into account and interesting results have been obtained for streamwise vortices by adopting the simplest possible ways, as a result, the pressure losses have been determined without the influence of travelling wave emerged only with the increase and decrease of wavelength and slope of meandering tube, respectively. Moreover, the linear stability theory has been implemented to trace the vertex formation. A decrease in wavelength creates the onset of flow separation near the surface of the tube. However, the stream has moved forward with a sudden disturbance by the meander which becomes rectilinear and the flow has become independent of vertex generating centrifugal forces. More precisely, a stream function is also found by using the standard and well-established relation. Effects of Reynolds number have been seen on the field variable and stream function, whereas, the results are shown in different plots.